How to identify a patient with autoinflammatory syndrome: Clinical and diagnostic algorithms - Mikhail Mikhailovich Kostik; L S Snegireva; M F Dubko; V V Masalova; T S Likhacheva; O V Kalashnikova; V G Chasnyk (Современная ревматология, 2013)
Autoinflammatory syndromes (AISs) are a group of predominantly hereditary diseases associated with the spontaneous uncontrolled production of proinflammatory cytokines. Most diseases are known to have molecular mechanisms and an inheritance pattern. The paper describes major AISs, such as familial Mediterranean fever; cryopyrin-associated periodic syndrome (familial cold urticaria, Muckle – Wells syndrome, CINCA/NOMID syndrome); tumor necrosis factor-α receptor-associated periodic syndrome; hyperimmunoglobulinemia D syndrome; periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis syndrome. An inheritance pattern and molecular defects are characterized for each disease. The principles of diagnosis and therapy are described. The role of interleukin-1 blockers in the therapy of AIS is defined. The most important symptoms that can be used to detect the major forms of AIS are identified. The Gaslini score, a special formula using the clinical symptoms to identify patients at high risk for AIS who need genetic typing and those at low risk for AIS, is described. A clinical diagnostic algorithm is presented, which can be used to detect patients with AIS and to determine indications to and the time of molecular genetic typing, and to choose priority genes.